Pengaruh Security, Brand Name dan Word of Mouth terhadap Brand Trust pada Pembelian Produk Nature Republic Soothing and Moisture Aloe Vera 92% Soothing Gel (Studi Kasus pada Mahasiswa FEB Unimal - Siti Maimunah; Rosita Rosita (Jurnal Visioner & Strategis, 2020)
The study aims to determine the effect of security, brand name and word of mouth on brand trust on the purchase of the nature republic soothing and moisturizing aloe vera product 92% soothing gel for students at the Faculty of Economics, Malikussaleh University. This study used primary data obtained by distributing questionnaires to all 96 respondents. The results of this study indicate that partially there are security, brand name and Word of mouth have significantly effect on brand trust. Simultaneously, security, brand name and word of mouth have an effect on brand trust on the purchase of a product of nature republic soothing and moisturizing aloe vera 92%  soothing gel on students of Economics and Business Faculty, Malikussaleh University.   Keywords: Security, Brand Name, Word of Mouth and Brand Trust